Pemberdayaan tentang Budaya Keselamatan dan Kesehatan Kerja (K3) pada Pekerja di Tempat Penampungan Barang Bekas - Sari Arlinda; Lindawati; Mahaza; Awaluddin; Suksmerri; Muklis (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
Workers in the informal sector, such as waste pickers, face significant health risks due to exposure to waste containing dangerous pathogens. In Kuranji District, Padang City, especially in Gunung Sarik and Kalumbuk Subdistricts, workers at scrap yards are involved in various work processes, including weighing, sorting and maintaining mechanical equipment. Working conditions in these places often do not meet safety standards, such as the lack of use of personal protective equipment (PPE) such as masks, boots, helmets and gloves. The aim of this activity is to empower workers at used goods storage to promote Occupational Safety and Health (K3). The activity methods are counseling and demonstrations, providing Personal Protective Equipment and Posters, and pretest and posttest questionnaires to measure public knowledge regarding K3 culture to reduce the risk of work accidents to workers. Results: there was an increase in knowledge after being given counseling and workers were enthusiastic about asking questions during the counseling process. Conclusion: It is important to provide empowerment and education regarding Occupational Safety and Health (K3) culture to workers at used goods shelters in Kuranji District, Padang City, to reduce risks and improve their welfare.